Pemberian Kompres Hangat dan Prenatal Massage untuk Mengurangi Nyeri Punggung pada Ibu Hamil Trimester III - Putri, Widyenti; Erlina, Erlina; Anjani, Arum Dwi; Aulia, Devy Lestari Nurul (Universitas Malahayati, 2025)
ABSTRACT The aim of this research is to find out and examine how providing complementary therapy can reduce back pain experienced by pregnant women in the third trimester by providing warm compresses and prenatal massage as carried out by previous researcher. One of the causes of lower back pain is due to hormonal changes that cause changes in muscle flexibility. One of the complementary therapies that can reduce or relieve pain, reduce or prevent muscle spasms, provide a sense of comfort, namely with warm compresses and prenatal massage. The research method used by the author is the literature review method, namely collecting literature sources in the form of articles and research journals with related themes, namely that providing complementary therapy can reduce back pain experienced by pregnant women in the third trimester by providing warm compresses and prenatal massage through an electronic database, namely Google. Scholar, using the keywords